MUSICAL INSTRUMENTS AND NATIVE LANGUAGE LEARNING AMONG RUNGUS IN SABAH, MALAYSIA - Romzi Ationg,; Madiyem Layapan,; Azizan Had,; Jelani Hamdan,; Saifulazry Mokhtar, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Native Language learning is a complex and remarkable achievement because the process generally emerges from unique interactions that distributed across social networks and is embodied in individuals. Accordingly, scholars portray the need of a specific approach in native language learning. Among the native learning approach identified is the ‘experiential learning’, an approach based on the idea of learning from experience as the path to lifelong learning and development. Scholars who is a fan of the learning approach argues that providing the learners an opportunity to learn through experience thus become immensely valuable. Some even specifically suggest that musical instruments can be used as a promising experience based instructional instrument in language learning. But how exactly the musical instruments affect native language learning process? Through the application of a mixed-method approach, this paper examines the relationship between musical instruments and the native language learning via the lens of Rungus in Sabah, Malaysia. It shows that the musical instruments affect the native language learning among Rungus in Sabah, Malaysia. What this now hinted is that the musical instruments are an important part of a successful native language learning process, thus made it clear the need among instructors to consider musical instruments as part of their teaching activities.